PENERAPAN METODE BAHTSUL MASAIL DALAM PEMBELAJARAN PAI UNTUK MENINGKATKAN KARAKTER RELIGIUS SISWA DI SMP ISLAM AL-FATH PLANTUNGAN KENDAL - Siti Amalia Cahyaning Haz; Ali Imron; Ahmad Khoiri (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
Strengthening students’ religious character has become a central concern in Islamic education at the secondary school level. Rapid social changes, shifts in students’ behavior, and the predominance of conventional teaching methods require innovative approaches in Islamic Religious Education learning. The Bahtsul Masail method, which emphasizes deliberation and the resolution of religious issues, is considered relevant to addressing these challenges. This study aims to examine the implementation of the Bahtsul Masail method in Islamic Religious Education learning and its implications for enhancing students’ religious character at SMP Islam Al-Fath Plantungan Kendal. A descriptive qualitative approach was employed. Data were collected through observation, interviews, and documentation involving the school principal, Islamic Religious Education teachers, and 32 ninth-grade students. Data analysis was conducted through data reduction, data display, and conclusion drawing. The findings indicate that the implementation of the Bahtsul Masail method was carried out in a structured manner and had a positive impact on students’ religious understanding, critical thinking skills, tolerance, and religious behavior. The main obstacles included students’ diverse backgrounds and a lack of seriousness among some students during discussions, while supporting factors comprised teachers’ roles, a conducive classroom environment, and students’ enthusiasm. These findings confirm that the Bahtsul Masail method is a relevant and effective strategy for fostering students’ religious character in Islamic Religious Education learning.